Kampung Kuta Religion: Social, Economic and Religious Structures of Indigenous Community in West Java - Husnul Qodim (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2019)
Kampung Kuta is one of the Sundanese traditional villages in West Java. They believe in the myth of the sacred forest and the origin of their ancestors which is preserved by the phrase of amanah and taboos. This article aims to analyze the indigenous religion of Kampung Kuta community. The study focuses on analyzing the relationship between social, economic and religious structures as its constituent elements. Using an ethnographic studies based on structural functionalism theory, this study shows that the religious construction of Kampung Kuta has a mutually influential relationship with both economic and social structures. The economic structure depends on the livelihoods of farming and gardening which are determined by the changing seasons and natural phenomenon. This then created religious structures that were magical and ritualistic. The people believe that the forest and their places are surrounded by cosmic forces of the Sacred. Various myths and beliefs in the common origins of ancestors influence the structure of social life to preserve the nature together. It can be reflected in the kinship system, social solidarity between relatives, social harmony and lifestyle of simplicity.